Navigating Economic Challenges in the Digital Photography andVideo Industry: An Analysis of Monetization Strategies ThroughSubscription Models and the Role of Online Platforms - Chitra Lestari, S.I.Kom, M.I.Kom, Chitra Lestari, S.I.Kom, M.I.Kom (Akademi Komunikasi SAE Indonesia, 2025)
The digital photography and video industry has undergone a significant transformation due to technological advancements and changes in consumer behavior. This research aims to analyze the industry's economic challenges and explore more effective monetization strategies through subscription models and the role of online platforms. The research method used was qualitative, employing a case study approach that involved semi-structured interviews and focus group discussions with industry players. The findings show that the main challenges include technological unemployment, financial constraints, and the complexity of digital marketing. The subscription model is a relevant monetization strategy to provide a steady revenue stream, while online platforms play an essential role in supporting monetization through influencer marketing and product sales. This research emphasizes the need for adaptation and innovation to enhance the sustainability of the digital photography and video industry in the digital era.